R&D Spillover and Predictable Returns - Jiang, Yi; Qian, Yiming; Yao, Tong (Review of Finance, 2016)
Abstract We show that firms’ R&D activities can predict the stock returns of their industry peers. When an industry experiences substantial R&D growth driven by the activities of a small group of firms, industry peers experience positive abnormal returns and abnormal operating performance despite having no aggressive R&D growth. Exogenous industry shocks to demand or productivity do not explain these results. Further, abnormal returns are concentrated in peer firms that receive low investor attention.